Effects of resistance training on arterial stiffness in healthy people: A systematic review - Garcia-Mateo, P.; Garcia-de-Alcaraz, A.; Rodriguez-Perez, M. A.; Alcaraz-Ibáñez, M. (Journal of Sports Science & Medicine, 2020)
The influence of aerobic training on cardiovascular disorders has already been demonstrated. However, the effect of resistance training is less well known. Arterial stiffness is an increasingly important measure in cardiovascular health. Therefore, this review attempted to study the results of resistance training-based interventions on arterial stiffness in healthy people, for both acute and chronic interventions. A literature search was conducted for randomized controlled trials on the acute and chronic effects of strength training. Studies published in PubMed and SportDiscus databases between 1999 and April 2019 were analyzed. In chronic strength training effects, the majority of groups showed large (d = -1.49 to -1.20) and moderate (d = -1.07) decreases, and small and trivial changes in arterial stiffness. In acute effects interventions, a very large decrease (d = -3.92) was observed, while large (d = 1.24-1.48) and very large (d = 3.88) increases were also found. A resistance training-based intervention of more than four weeks` duration with a frequency of two days per week seems not to compromise cardiovascular health, due to decreases in arterial stiffness. However, there is a general trend towards both increasing and maintaining arterial stiffness after isolated strength training sessions.